A young woman with numbness in her feet. Issue 12 (December 2016) - Pavlik, Daniel; Huber, Michael; Justice, Melissa
Abstract : ABSTRACT: This article describes a young, otherwise healthy woman who presented to the ED with numbness in her feet and was discharged. Twenty-four hours later, she returned because of difficulty walking; in 48 hours she could not walk without assistance. Although Guillain-Barré syndrome was suspected initially, the patient's weakness, sensory loss, and autonomic dysfunction eventually were diagnosed as transverse myelitis, a myelopathy often associated with infectious or autoimmune diseases. The article describes the presentation, diagnostic evaluation and criteria, treatment, and prognosis of transverse myelitis.